2011
DOI: 10.1038/embor.2011.223
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the haematopoietic niche regulates the cellular immune response in Drosophila

Abstract: Oxidative stress induced by high levels of reactive oxygen species (ROS) is associated with the development of different pathological conditions, including cancers and autoimmune diseases. We analysed whether oxidatively challenged tissue can have systemic effects on the development of cellular immune responses using Drosophila as a model system. Indeed, the haematopoietic niche that normally maintains blood progenitors can sense oxidative stress and regulate the cellular immune response. Pathogen infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
161
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 37 publications
3
161
0
Order By: Relevance
“…Similar observations were made in col larvae (10,12) and it was shown that wasp infection causes an increase in NF-κB signaling (30), ROS levels and Eiger expression in the PSC (14), leading to lamellocyte differentiation. Thus, the PSC seems required as a relay for mounting the cellular immune response to parasitic wasp infestation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar observations were made in col larvae (10,12) and it was shown that wasp infection causes an increase in NF-κB signaling (30), ROS levels and Eiger expression in the PSC (14), leading to lamellocyte differentiation. Thus, the PSC seems required as a relay for mounting the cellular immune response to parasitic wasp infestation.…”
Section: Discussionsupporting
confidence: 79%
“…It was thus proposed that the PSC provides a microenvironment that supports hematopoietic progenitor maintenance in the LG (10,11). In line with this model, increasing or decreasing PSC size/activity can, respectively, impede or promote hemocyte differentiation (11,(13)(14)(15)(16)(17)(18)(19). However, differentiated hemocytes are frequently observed close to the PSC, and it is unclear how progenitor fate is maintained in the posterior lobes, which are far apart and physically separated from the PSC.…”
mentioning
confidence: 99%
“…The importance of a certain level of ROS production during differentiation has been discussed, and specific roles in regulating stem cell activity in hematopoietic stem cell niches have been shown in mammals (Simon and Keith, 2008). Moreover, detailed studies in Drosophila have revealed an important role for ROS production in the induction of lamellocyte differentiation (Owusu-Ansah and Banerjee, 2009;Sinenko et al, 2012). In P. leniusculus, ROS production is primarily regulated in the APC, and recent experiments have shown that this ROS production is associated with differentiation, affecting the structure of the extracellular matrix surrounding the hematopoietic precursors (Junkunlo, 2015).…”
Section: The Anterior Proliferation Center (Apc) Is An Important Partmentioning
confidence: 99%
“…In Drosophila, high ROS levels were detected in hematopoietic progenitor cells, and increased ROS levels were detected in the posterior signaling center of the lymph gland after a wasp infestation (23). In the fly, ROS serve as an important signal for progenitor cell differentiation into lamellocytes, a hemocyte type that encapsulates wasp eggs (24,25). In crayfish, a high level of ROS was detected in the APC, where actively proliferating cells are located (6).…”
mentioning
confidence: 99%